Dyplomacja lotnicza i kosmiczna – aspekty prawne - Małgorzata Polkowska (Acta Iuris Stetinensis)
Aerospace diplomacy has its own peculiarities due to the complex subject of regulation, which is to ensure security, both in air and space. The plane of air and space diplomacy can be referred not only to the creation of international legal norms or cooperation within the framework of international organizations, but also more broadly to other activities related to the cooperation of states. This diplomacy draws its foundations, essence and principles from public international law, of which diplomatic and consular law and diplomatic protocol are a part. Much attention was paid to issues related to the activities of international aviation and space organizations, which create a formal framework for international cooperation in the researched field. It is of great theoretical and practical importance to present the process of creating international conventions, during which the views of people and the positions of the delegating states clash. The author is looking for answers to research questions: whether and how changes in diplomacy, including virtual diplomacy, contribute to achieving the goals set by international organizations and individual countries? The author unequivocally points to the important role of international law in counteracting the unlawful seizure of air and outer space. He does so by discussing the rich achievements of international and Polish doctrine of international law, using her own experience of working in the International Civil Aviation Organization as Polish Representative in the ICAO Council.